Correlation between D-dimer and first-ever acute ischemic stroke (AIS) severity in Dr. Sardjito General Hospital, Yogyakarta - Abdul Gofir; Hiztien Fahrurriza; Yudhanto Utomo; Amelia Nur Vidyanti; Anton Darmawan (Published by Universitas Gadjah Mada, 2025)
Acute ischemic stroke (AIS) continuing to be an entity causing morbidity and mortality worldwide. The National Institutes of Health Stroke Scale (NIHSS) is a largely used as clinical assessment instrument to measure neurological deficit of stroke. Studies concerned that D-dimer, a fibrin degradation product, has as a potential biomarker in predicting stroke severity and prognosis. This study aimed to investigate the correlation between D-dimer levels and NIHSS score in patients with a first-ever AIS. This cross-sectional study used the stroke registry data of the Dr. Sardjito General Hospital, Yogyakarta from October 2021 to December 2022. A total 83 patients who met the inclusion and exclusion criteria were involved. The blood D-dimer level was measured during admission. The NIHSS scores were assessed within 24 hr of admission. The correlation between D-dimer levels and NIHSS scores were analysed using Spearman’s test. Multiple analysis was performed to evaluate the association of non-dependent risk factors using multiple logistic regression. The mean age of subjects was 60.77±11.08 yr, with a slightly males predominant (54.2%). The mean value of NIHSS score was 6.59 ± 7.00 and D-dimer level was 712.02 ± 1159.2 ng/mL. A significant positive correlation between D-dimer and NIHSS score (r= 0.475; p= 0.01) was observed. Furthermore, D-dimer remained showing an independent association with on-admission NIHSS score (p= 0.026). In conclusion, D-dimer level in stroke patients is associated with more severe on-admission NIHSS score.